Long-Term Outcomes of the Treatment of Unresectable (StageIII-IV) Ductal Pancreatic Adenocarcinoma Using Metabolically Supported Chemotherapy (MSCT): A Retrospective Study - (:unkn) unknown (E S BURIONI RICERCHE BIBLIOGRAFICHE, 2016)
Introduction Metabolically supported chemotherapy, is defined as the application of standard chemotherapy protocols concomitant to the administration of pharmacological doses of regular insulin and the development of hypoglycemia, and following fasting starting the previous day. This study aims to present the effects of metabolically supported chemotherapy on the overall survival of locally advanced and metastatic (stage III and stage IV, respectively), or simply unresectable pancreatic adenocarcinoma patients. Material and methods This study is a retrospective analysis of a prospectively maintained database of patients. It includes all patients that applied to our clinic between July 2012 and December 2014 that were diagnosed with unresectable (stage III-IV) pancreatic adenocarcinoma. The demographic data of all the patients as well as the chemotherapy regimen received, date of treatment initiation, date of disease remission, mortality and overall survival of all patients were analyzed using SPSS 20.0. Patient follow-up was performed by means of computed tomography and positron emission tomography-computed tomography scans. Results 33 patients, 24(73%) males and 9(27%) females, were included in our study. The majority, 27(81%) patients, had metastatic disease at the time of diagnosis and were stage IV. While 11(33%) of the patients were treated using a gemcitabine-based protocol, 13(39%) received FOLFIRINOX. 9(27%) of the patients were initially treated using gemcitabine, but began receiving FOLFIRINOX following progression as second-line chemotherapy. Statistical analysis revealed a median survival of 19.5 months and a 1-year survival rate of 82.5%. Presently, 18(54%) of the patients remain healthy and alive, free of disease progression with eastern cooperative oncology group performance statuses ranging between Grade 0 -1. 4(22%) of these patients ultimately underwent radical pancreatic surgery: 3(17%) having undergone pancreaticoduodenectomies (Whipple procedures) and 1(5%) having undergone a distal pancreatectomy. Conclusion This study demonstrates that a metabolically supported form of applying standard chemotherapy regimens may enhance the overall survival rates of unresectable (stage III-IV) pancreatic adenocarcinoma patients.
Keywords: Adenocarcinoma; Antineoplastic Combined Chemotherapy Protocols; drug therapy; Insulin; mortality; Pancreatic Neoplasmsphysiology; Survival Analysis; therapeutic use; PHASE-III; GROWTH-FACTORS; CANCER; INSULIN; GEMCITABINE; OXALIPLATIN; SURVIVAL; THERAPY